IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NO. 20 TAHUN 2018 TENTANG PELAPORAN DAN PERTANGGUNGJAWABAN APBDes DI DESA LUBUK MINDAI BENGKULU UTARA - Sulisti Afriani; Zahrah Indah Ferina (Jurnal Ilmu Akuntansi, 2020)
This study aims to determine the Village Financial Management in Lubuk Mindai Village, North Bengkulu. The object of this research is in the village of Lubuk Mindai, North Bengkulu. This type of research is qualitative research. This research was conducted using interview and documentation techniques with parties involved in the management of ADD. The description results are obtained through Permendagri No. analysis. 20 of 2018 by comparing the realization in the field. Village financial management in Lubuk Mindai North Bengkulu Village in 2019 began reporting and accountability stages. Broadly speaking, it can be said to be in accordance with Permendagri No. 20 of 2018.